The role of omega-3 fatty acids, vitamins and minerals in cognition, mood and the perception of food. - Sara Jayne Long (2013)
Previous research has suggested a role for nutrients in several aspects of psychological functioning. Based on this research the present thesis explored the role of omega-3 fatty acids, vitamins and minerals in cognition, mood and the perception of food. Divided into three sections, the first section of the thesis used qualitative methods to explore factors that affected food choice and the decision to consume a healthy diet (i.e. a diet high in omega-3, vitamins and minerals). In addition, factors that affected supplement use, specifically the factors that affected the use of omega-3 fatty acid, vitamin and mineral supplements were explored. From the data, two models were developed: one depicting factors that influenced food choice and healthy eating, and one depicting factors that influenced supplement use. After the examination of the factors that affected food choice, healthy eating and the consumption of omega-3 fatty acids, vitamins and minerals, the importance of these nutrients in psychological health and cognition was explored in a double-blind, randomized controlled trial. Specifically the second section explored the effect of vitamins, minerals, and/or omega-3 fatty acids in mild psychiatric symptoms, stress, aggression, impulsivity, fatigue, hostility, anxiety, confusion, confidence, reaction time, memory and vigilance. A positive response was found to DHA with regard to aggression and response inhibition; in addition there was a trend for those taking only DHA to report feeling more clearheaded the taking of vitamins/minerals alone resulted in feeling more clearheaded. Supplementation with vitamins and minerals was found to significantly reduce stress. With the General Health Questionnaire the difference between the placebo and vitamins/minerals groups approached statistical significance. There was no effect of omega-3, vitamins and minerals of any cognitive domain (memory, reaction time and vigilance). Although it was concluded that on occasions either vitamins/minerals or DHA when tested alone had a positive effect on mood, stress and mild psychiatric symptoms, there was no synergistic interaction; rather on occasions the interaction between these supplements had negative consequences. The third section explored the role of omega-3 fatty acids, vitamins and minerals in the perception of food, specifically the effects of enrichment, health claim and gender on three variables involved in consumer behaviour: the perceived healthiness, the desirability of supplementation and the likelihood of purchase of foods. The main findings were that i) health claims increased the perceived healthiness of unhealthy foods; ii) the likelihood of purchase increased mostly after the enrichment of healthy foods (which is consistent with some findings but not others), iii) males were more likely to purchase healthy, high protein products than females. Besides these findings there was no consistent effect of enrichment, health claim or gender on the 3 facets of consumer behaviour, suggesting that the effects on the 3 consumer variables should be considered individually. In addition, when examining the role of gender males and females should be considered separately.